Estimating the mirror seeing for a large optical telescope with a numerical method. (May 2018) - Zhang, En-Peng; Cui, Xiang-Qun; Li, Guo-Ping; Zhang, Yong; Shi, Jian-Rong; Zhao, Yong-Heng
Abstract: It is widely accepted that mirror seeing is caused by turbulent fluctuations in the index of air refraction in the vicinity of a telescope mirror. Computational Fluid Dynamics (CFD) is a useful tool to evaluate the effects of mirror seeing. In this paper, we present a numerical method to estimate the mirror seeing for a large optical telescope (∼ 4 m) in cases of natural convection with the ANSYS ICEPAK software. We get the FWHM of the image for different inclination angles ( i ) of the mirror and different temperature differences (Δ T ) between the mirror and ambient air. Our results show that the mirror seeing depends very weakly on i, which agrees with observational data from the Canada-France-Hawaii Telescope. The numerical model can be used to estimate mirror seeing in the case of natural convection although with some limitations. We can determine Δ T for thermal control of the primary mirror according to the simulation, empirical data and site seeing.